Financial Strength, Financial Performance and Firm’s Value in Multinational Companies in Nigeria - OSHO, Augustine E. (Acta Universitatis Danubius. Œconomica, 2022)
This study examined the relationship between financial strength, financial performance and firm’s value of multinational companies in Nigeria. The main objective of the study is to study the effects of financial strength and financial performance on firm’s value of a multinational company in Nigeria. This Study is based on signally theory. Secondary sources of data were sourced from Central Bank of Nigeria Statistical Bulletin and annual report of the selected multinational company in Nigeria. Ordinary Least Square Linear Regression model was used in analyzing the data. Findings show Quick Ratio (QR) has a significant positive relationship with firms’ values, Debt to Equity Ratio (DER) has a significant negative relationship with Firms’ values, Debt to Assets Ratio (DAR) has a significant positive relationship with Firms’ values while Cash Flow Ratio has a significant positive relationship with firms’ values as proxies for financial strength. Return on Capital Employed (ROCE) as proxy for financial performance has a significant positive relationship with firms’ values of multinational companies in Nigeria. The study concluded that, if multinational companies build strong financial strength to improve their financial performances, their market value would be sustained.